Optical and Electrical Characterization of Crystallized M:WO3 (Cu, Fe, Ni) Films in Acidic Medium - Irmak Karaduman Er; Fatma Sarf; Emin Yakar (Journal of Advanced Research in Natural and Applied Sciences)
Pure and metal (M) doped [copper (Cu), nickel (Ni) and iron (Fe)] WO3 films have been produced on In:SnO2 (ITO) slides by using facile chemical bath deposition and then annealed at 500 oC for 2 h. Structural, morphological, electrical and optical properties of the produced WO3-based films were examined. Monoclinic WO3 phase were observed in all the samples, and the peak intensities were decreased by metal inclusion with heterogeneous film growth on ITO substrate. Slight shifts from defect related emission peaks (blue and green) were observed in metal-substituted WO3 samples from PL study. An optical band gap was observed to decrease in M:WO3 samples. The surface resistance values were significantly reduced by metal additives compared to its pure counterpart, especially by the inclusion of nickel ions in WO3. The results indicated that nucleus growth and thereby impurity/defect-related surfaces had a serious effect on the optical and electrical properties of M:WO3 films.